Investigation of Groundwater and The Impact of Over-Pumping in Al-Haydariyah Region, Iraq (Journal of Engineering, 2023)
In this study; a three-dimensional model was created to simulate groundwater in Al-Haydariyah area of the governorate of Al-Najaf. A solid model was created to utilize the cross sections of 25 boreholes in the research region, and it was made out of two layers: sand and clay. The steady-state calibration was employed in six observation wells to calibrate the model and establish the hydraulic conductivity, which was 17.49 m/d for sand and 1.042 m/d for clay, with a recharge rate of 0.00007 m/day. The wells in the research region were reallocated with a distance of 1500 m between each well, resulting in 140 wells evenly distributed throughout the study area and with a discharge of 5 l/s, and the scenarios were run for 1000 days to explore the impact of over-pumping on groundwater levels. The wells were operated at three different operating hours: 4, 8, and 12 h/d. According to the results, the largest water table decrease for each scenario was 0.35, 8.25, and 8.68 m, respectively. It was discovered that the first scenario, with an operating duration of 4 h/day and a discharge of 72 l/s, was the best scenario in which dry cells did not happen.